Lifestyle factors and oxidative stress in female infertility: is there an evidence base to support the linkage?. (November 2013) - Gupta, Sajal; Fedor, Jennifer; Biedenharn, Kelly; Agarwal, Ashok
At present, between 10 to 15% of couples are infertile, and half of all infertility cases are credited to a female factor. Determination of the source of the problem may hold the key to improving fertility for women. Emerging research demonstrates that reactive oxygen species and oxidative stress (OS) have strong connections with female reproductive function; increases in OS which is associated with certain lifestyle factors can negatively impact female fertility. Lifestyle factors including being obese or underweight, exercising, cigarette smoking, alcohol and caffeine consumption, drug use, psychological stress and environmental and occupational exposures can all have adverse effects on fertility due to their complex interactions and impact exerted via OS on female reproductive processes. Our review highlights these linkages to explain their impact on female fertility, as well as provide suggestions to reduce OS and improve reproductive potential in women.